"I address race because race addresses me": women of color show receipts through digital storytelling. Issue 1 (2nd January 2021) - Brekke, Anjuli Joshi; Joseph, Ralina; Aaftaab, Naheed Gina
ABSTRACT: In Black colloquial culture, the practice of documenting and calling out injustices is known as "showing receipts." The ongoing labor of collecting, communicating, and showing receipts is one way to highlight the hypocrisies embedded in racist structures and hold those in power accountable. As the receipts pile up in the form of viral videos of sexism, racism, and violence against Black bodies, accountability cannot be easily ignored. Showing receipts as a form of resistance, however, is both exhausting and never-ending. Thus, women of color need spaces of respite and community care where we can speak our stories and be heard. In this essay, we demonstrate one such space: digital storytelling shared between women of color. While reciprocal sharing provides women of color storytellers a respite from the labor of proving our worth and producing receipts, in recording our truths and sharing them online, we also create digital receipts as testimony to our experiences. Although there is no guarantee that those in power will listen, by producing, archiving, and disseminating these receipts, storytellers maintain hope that our words will make an impact.